A camera never told the truth: An exploration of objectivity in photojournalism - Rehman, Sharaf N. (Annales. Etyka w Życiu Gospodarczym, 2019)
Several cases have surfaced in the past two decades where the photojournalists associated with some of the most respected and trusted news organizations have been accused of altering the news photos. During the same time, the developments in the digital cameras and editing software have put the image altering technology into the hands of all practicing journalists and journalism students. This paper explores two, somewhat connected, issues: objectivity in photojournalism and ethics of altering photographic images. The paper discusses objectivity in journalism in general and photojournalism to address the question: Can a photojournalist use a camera to record reality in an objective manner? Since the photographers have altered (retouched) images from the very beginning of photography, where are the ethical boundaries of image alteration for the photojournalists?